Collapsing glomerulopathy is likely a major contributing factor for worse allograft survival in patients receiving kidney transplants from black donors - DiFranza, Lanny T.; Daniel, Emily; Serban, Geo; Thomas, Steven M.; Santoriello, Dominick; Ratner, Lloyd E.; D’Agati, Vivette D.; Vasilescu, Elena-Rodica; Husain, Syed Ali; Batal, Ibrahim (Frontiers in Medicine, 2024)
Although a few registry-based studies have shown associations between receiving kidney allografts from Black donors and shorter allograft survival, detailed, large, single-center studies accounting for common confounding factors are lacking. Furthermore, pathologic alterations underlying this potential disparity have not been systematically studied. We performed a retrospective clinical-pathological study of kidney transplant recipients who received kidney allografts from either Black (n=407) or White (n=1494) donors at Columbia University Irving Medical Center from 2005-2018, with median follow-up of 4.5 years post-transplantation. Black donor race was independently associated with allograft failure (adjusted HR=1.34, P=0.02) and recipients of kidney allografts from Black donors had a higher incidence of collapsing glomerulopathy [7.4% vs. 1.9%, OR=4.17, P<0.001]. When causes of allograft failure were examined, only allograft failure following development of collapsing glomerulopathy was more frequent in recipients of allografts from Black donors [15% vs. 5%, OR=3.16, P=0.004]. Notably, when patients who developed collapsing glomerulopathy were excluded from analysis, receiving kidney allografts from Black donors was not independently associated with allograft failure (adjusted HR=1.24, P=0.10). These findings revealed that, compared with recipients of kidney allografts from White donors, recipients of kidneys from Black donors have modestly shorter allograft survival and a higher probability of developing collapsing glomerulopathy, which negatively impacts allograft outcome. Identification of collapsing glomerulopathy risk factors may help decrease this complication and improve allograft survival, which optimally may reduce racial disparities post-transplantation.